Fast preparative separation of flavones from capitula of Eriocaulon ligulatum (Vell.) L.B.Smith (Eriocaulaceae) by High-speed countercurrent chromatography (HSCCC) - Santos, Lourdes Campaner dos [UNESP]; Silva, M. A. [UNESP]; Rodrigues, C. M. [UNESP]; Rodrigues, J. [UNESP]; Rinaldo, D. [UNESP]; Sannomiya, M. [UNESP]; Vilegas, Wagner [UNESP] (My University, 2005)
High-speed countercurrent chromatography (HSCCC) is a leading method for the fast separation of natural products from plants. It was used for the preparative isolation of two flavone monoglucosides present in the capitula of Eriocaulon ligulatum (Veil.) L.B.Smith (Eriocaulaceae). This species, known locally as botão-dourado, is exported to Europe, Japan and North America as an ornamental species, constituting an important source of income for the local population of Minas Gerais State, Brazil. The solvent system, optimized in tests prior to the HSCCC run, consisted of the two phases of the mixture ethyl acetate: n-propanol: water (140:8:80, v/v/v), which led to the successful separation of 6-methoxyluteolin-7-O-β-D-allopyranoside and 6-methoxyapigenin-7-O-β-D-allopyranoside in only 3 hours. The two flavonoids were identified by NMR (1-D and 2-D) and ESI-MS, comparing their spectra with published data.
Keywords: E. ligulatum; Eriocaulaceae; Flavone; HSCCC; 6 methoxyapigenin 7 o beta dextro allopyranoside; 6 methoxyluteolin 7 o beta dextro allopyranoside; acetic acid ethyl ester; flavanoid; propanol; unclassified drug; water; chemical structure; counter current chromatography; electrospray mass spectrometry; nuclear magnetic resonance